2022
DOI: 10.3390/molecules27207042
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effects of Genistein In Vitro as a Chemopreventive Agent for Colorectal Cancer—Strategy to Improve Its Efficiency When Administered Orally

Abstract: Colorectal Cancer (CRC) ranks third in terms of incidence and second in terms of mortality and prevalence worldwide. In relation to chemotherapy treatment, the most used drug is 5-fluorouracil (5-FU); however, the use of this drug generates various toxic effects at the systemic level. For this reason, new therapeutic strategies are currently being sought that can be used as neoadjuvant or adjuvant treatments. Recent research has shown that natural compounds, such as genistein, have chemotherapeutic and antican… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…Our data showed a concentration-dependent (10-75 µM) reduction in HCT-116 cells' viability (Figure 1), significant alterations of cellular morphology, a slight inhibitory effect on HCT-116 cells' migratory capacity, and the reorganization of actin cytoskeleton and nuclear changes. These results are supported by other studies that demonstrated the anticancer effects of genistein in different colon cancer cells exerting multiple mechanisms of action, as follows: (i) in HT-29 and SW620 cells, genistein decreased cells' viability and increased oxidative stress and inflammation [30]; (ii) in HT29 cells, genistein suppressed cells' migration and invasion by inducing demethylation and recovering the activity of WNT inhibitory factor 1 (WIF1), a tumor suppressor [15]; (iii) in SW480 and SW620 cells, genistein triggered a dose-dependent antiproliferative effect and inhibited cells' viability via apoptosis [14]; (iv) in HCT-116 cells, genistein induced apoptosis and suppression of cells' proliferation by interfering with miR-95, Akt and SGK1 signaling transduction pathways [12], (v) in SW480, genistein treatment caused cell cycle arrest, inhibition of cells' proliferation, and histone acetylation [31]; and (vi) in HCT-116 and LoVo cells, genistein induced the mitochondrial pathway of apoptosis by suppressing phosphorylation of Akt [32], etc. The anticancer potential of genistein was also proved in other preclinical models of breast cancer, gastric cancer, hepatocellular carcinoma, and salivary adenoid cystic carcinoma [27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our data showed a concentration-dependent (10-75 µM) reduction in HCT-116 cells' viability (Figure 1), significant alterations of cellular morphology, a slight inhibitory effect on HCT-116 cells' migratory capacity, and the reorganization of actin cytoskeleton and nuclear changes. These results are supported by other studies that demonstrated the anticancer effects of genistein in different colon cancer cells exerting multiple mechanisms of action, as follows: (i) in HT-29 and SW620 cells, genistein decreased cells' viability and increased oxidative stress and inflammation [30]; (ii) in HT29 cells, genistein suppressed cells' migration and invasion by inducing demethylation and recovering the activity of WNT inhibitory factor 1 (WIF1), a tumor suppressor [15]; (iii) in SW480 and SW620 cells, genistein triggered a dose-dependent antiproliferative effect and inhibited cells' viability via apoptosis [14]; (iv) in HCT-116 cells, genistein induced apoptosis and suppression of cells' proliferation by interfering with miR-95, Akt and SGK1 signaling transduction pathways [12], (v) in SW480, genistein treatment caused cell cycle arrest, inhibition of cells' proliferation, and histone acetylation [31]; and (vi) in HCT-116 and LoVo cells, genistein induced the mitochondrial pathway of apoptosis by suppressing phosphorylation of Akt [32], etc. The anticancer potential of genistein was also proved in other preclinical models of breast cancer, gastric cancer, hepatocellular carcinoma, and salivary adenoid cystic carcinoma [27].…”
Section: Discussionmentioning
confidence: 99%
“…The anticancer potential of genistein was also proved in other preclinical models of breast cancer, gastric cancer, hepatocellular carcinoma, and salivary adenoid cystic carcinoma [27]. The main advantage of genistein is the low/non-toxic profile [14,33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Colorectal cancer (CRC) ranks third in terms of global cancer incidence as reported by WHO. Additionally, it is ranked as the second most prevalent cause of cancer‐related mortality on a global scale 1 . It is anticipated by the International Agency for Research on Cancer (IARC) that the newly diagnosed cases of CRC will exceed the figure of 3 million each year by 2040 2 …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it is ranked as the second most prevalent cause of cancerrelated mortality on a global scale. 1 It is anticipated by the International Agency for Research on Cancer (IARC) that the newly diagnosed cases of CRC will exceed the figure of 3 million each year by 2040. 2 A colorectal polyp is an abnormal non-cancerous tissue growth that extends towards the lumen of the colon and rectum from the mucosal lining.…”
Section: Introductionmentioning
confidence: 99%